User councils for disabled people in Norway – from reactive to proactive? - Jan Andersen (Scandinavian Journal of Disability Research, 2015)
User councils act as advisory bodies for the agencies with which they are associated. This article is based on interviews with user participants and agency representatives from a sample of user councils in Norway. The main question raised is how user participation functions in user councils. In general, the findings show that among the user councils there are active discussions, most of the user informants feel that they are respected as equal partners and that they are taken seriously. However, the work is characterized by representatives from the agencies taking the initiative to raise issues and the user representatives responding to these initiatives, and in that way the user participants function reactively. Most of the informants from the agencies want the user representatives to be more active and critical. This raises concerns about how user participants can be more proactive. Finally, some prerequisites for improving the functioning of user councils are discussed.